(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study examined the impact of two error correction strategies on senior secondary school students’ achievement in Economics in Udenu Local Government Area, Enugu State. A quasi-experimental design with non-equivalent pretest and posttest control groups was employed, involving 933 SS2 Economics students (430 males and 503 females). A sample of 120 students from four secondary schools was selected using multi-stage sampling. The Economics Achievement Test (EAT), developed and validated for data collection, showed a reliability index of 0.98 from a trial test in Nsukka. Mean, Standard Deviation, and Analysis of Covariance (ANCOVA) at a 0.05 significance level were used for data analysis. The findings revealed that students taught using the students’ correction strategy achieved higher scores than those taught with the teacher correction strategy. Both strategies improved student achievement, but the students’ correction strategy was more effective for both male and female students. The study recommended that Economics teachers be trained by the Ministry of Education on using both error correction strategies to enhance student achievement. The major implication is that adopting the students’ correction strategy in teaching Economics can significantly boost students’ academic performance.